Microstructure and Some Properties of Aluminum-Silicon Matrix Composites Reinforced by Alumina or Chromia - Ahmed A. Moosa (Al-Khwarizmi College of Engineering – University of Baghdad, 2010)
In this work, yttrium oxide particles (powder) reinforced AL-Si matrix composites (Y2O3/Al-Si) and Chromium oxide particles reinforced AL-Si matrix composites (Cr2O3/AL-Si) were prepared by direct squeeze casting. The volume percentages of yttrium oxide used are (4, 8.1, 12.1, 16.1 vol %) and the volume percentages of the chromium oxide particles used are (3.1, 6.3, 9.4, 12.5 vol. %). The parameters affecting the preparation of Y2O3/Al-Si and Cr2O3/AL-Si composites by direct squeeze casting process were studied. The molten Al-Si alloy with yttrium oxide particles or with chromium oxide particles was stirred again using an electrical stirrer at speed 500 rpm and the molten alloy was poured into the squeeze die cavity. The pouring temperature that used for all castings is (700)˚C. The required squeeze pressure, 53 MPa, was then applied for 30 seconds at a delay time of 5. The die temp is (200˚C). The Y2O3/Al-Si composites and Cr2O3/Al-Si composites produced by squeeze casting have more microstructure refinement, higher hardness and lower wear rate than the unreinforced alloy.